2021
DOI: 10.3389/fmars.2021.778301
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Methanotroph (Methylococcus capsulatus, Bath) Bacteria Meal (FeedKind®) as an Alternative Protein Source for Juvenile Black Sea Bream, Acanthopagrus schlegelii

Abstract: Single-cell proteins are attracting growing attention as viable alternatives for fishmeal (FM) in aquatic feed. Methanotroph (Methylococcus capsulatus, Bath) bacteria meal FeedKind® (FK) is a type of single cell protein with high protein content (75.14%) and desirable amino acids profile, produced by Methylococcus capsulatus (Bath) living on methane consumption. The present study evaluated the potential of replacing FM with FK in the diet of black sea bream (Acanthopagrus schlegelii). Five iso-energetic and is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 83 publications
0
8
0
1
Order By: Relevance
“…To date, there have been more than 20 publications that demonstrate that these methane-oxidizing bacteria meal are safe, effective and with low carbon footprint in livestock and aquatic animal feed [ 9 , 16 ]. In general, FK can be used at 4~13% of total diet to replace equivalent amount of FM in fish and shrimp feed with positive or equivalent effects on survival and growth performance [ 17 , 18 , 19 , 20 , 21 , 22 ]. Interestingly, the inclusion of 300 mg of M. capsulatus per kg of feed could prevent the development of dietary soybean meal induced intestinal inflammation in Atlantic salmon [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, there have been more than 20 publications that demonstrate that these methane-oxidizing bacteria meal are safe, effective and with low carbon footprint in livestock and aquatic animal feed [ 9 , 16 ]. In general, FK can be used at 4~13% of total diet to replace equivalent amount of FM in fish and shrimp feed with positive or equivalent effects on survival and growth performance [ 17 , 18 , 19 , 20 , 21 , 22 ]. Interestingly, the inclusion of 300 mg of M. capsulatus per kg of feed could prevent the development of dietary soybean meal induced intestinal inflammation in Atlantic salmon [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…24 Regardless of the production conditions, these C1GP products, such as KnipBio meal, Bioprotein and RichMore, have an equivalent gross energy to fishmeal, that is, ranging from 21 to 22 MJ/kg. 34,35,64 For ash content, the slightly higher content of ash in methanol-utilizing gas protein, representing more than 8.5% ash in PRUTEEN and KnipBio meal, 27,34 compared to certain previous studies in methane-utilizing gas protein ranging from 6.3 to 8.0% [63][64][65][66] and RichMore ranging from 3.3 to 6.4%. 62,67,68 One previous study showed that the String Pro contained about 3.8% crude fibre and 3.3% carbohydrate, 63 while another study in mink reported that bacterial protein meal grown on natural T A B L E 2 Amino acid composition of C1 gas protein products compared with fishmeal (% of dry matter) The data are gotten from the web of https://www.feedipedia.org/ node/208.National.…”
Section: Glutamatementioning
confidence: 87%
“…As one of the earliest available C1GP products, methane-utilizing gas protein products have been used as fishmeal alternatives in the diet of different aquatic species, including Atlantic salmon, Salmo salar, 26 Atlantic halibut, Hippoglossus hippoglossus, 74 rainbow trout, Oncorhynchus mykiss, 71 Japanese yellowtail, Seriola quinqueradiata, 75 Nile tilapia, 83 black sea bream, 65 largemouth bass 84 and Pacific white shrimp. [85][86][87][88] Studies in Atlantic salmon 70,77,89 have reported that fish fed diets containing up to 300 g/kg Bioprotein did not negatively affect growth performance or enhanced growth performance in certain studies.…”
Section: Growth Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The formulation and approximate compositions of the experimental diets are shown in Table 1. Feed pellets with a diameter of 1.20 mm were prepared and steam-sterilized according to the specific production process described in previous study (Xu et al, 2021).…”
Section: Yarrowia Lipolytica Production and Experimental Diet Formula...mentioning
confidence: 99%